STRATEGI PENGEMBANGAN DESA WISATA KIARASARI MELALUI PENCIPTAAN BUKU PROFIL POTENSI WISATA DESA YANG BERKELANJUTAN - Candra Karismawan; Rahmat Darmawan; Jenal Abidin; Lala Siti Sahara (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
Kiarasari Tourism Village in Sukajaya District, Bogor Regency possesses various natural, cultural, and artificial tourism potentials that can be developed as a community-based tourism destination. However, the development of the tourism village still faces several challenges, particularly the lack of information media, limited destination publication, and the absence of systematic documentation of tourism potentials. This study aims to identify the tourism potentials of Kiarasari Village and analyze the preparation of a tourism potential profile book as a strategy for tourism village development and promotion. This study employed a descriptive qualitative method consisting of four stages: field surveys, data collection, in-depth interviews, and data analysis. Data were collected through field observations, documentation, literature studies, and interviews with the Tourism Village Working Group (Pokja), local communities, and village officials. The findings reveal that Kiarasari Village has diverse tourism potentials, including natural attractions such as waterfalls, rice fields, rivers, and camping grounds; cultural attractions in the form of local traditions and community activities; and artificial attractions such as tourism facilities and recreational areas. The study also indicates that the preparation of a tourism potential profile book serves as an important strategy to support destination documentation, promotion, and branding in a more systematic and informative manner. The profile book was designed using visual and descriptive approaches containing village profiles, tourism potentials, tourism facilities, local MSME products, and documentation of community activities. The existence of the profile book is expected to enhance the visibility of Kiarasari Tourism Village, strengthen destination identity, and support sustainable community-based tourism development.